Patient Perspectives of Health Care Teams: A Narrative Review - Crystal Guo; Roaa M. Khinkar; Shehnaz Alidina; Isaac S. Chua; Michaela J. Kerrissey (Medical Care Research and Review, 2026)
Patients engage in teamwork in health care, yet their perspectives on teams remain understudied compared with those of health care professionals. We conducted a narrative review to describe how patients experience and perceive engagement with health care teams. Of 633 articles screened from MEDLINE/PubMed (2010–2024; English), 76 studies met the inclusion criteria. Most were small-sample qualitative studies with little interconnection. They identified 58 team factors that we synthesized into a conceptual model of structures (e.g., expertise mix), processes (e.g., communication), and normative or affective features (e.g., trust). These factors shape outcomes through both patients’ perceptions of their team and patients’ own engagement. We conclude that patient perspectives on teams elicit important information about health care team functioning and are vital to represent in research and practice. There is a need for a cohesive, conceptually grounded representation of patient-perceived teamwork factors and research that tests teamwork interventions using outcome measures.